2022
DOI: 10.3389/fimmu.2021.797336
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Is Common in Immunoglobulin G Subclass Deficiency and Correlates With Inflammatory Response and Need for Immunoglobulin Replacement Therapy

Abstract: PurposeIndividuals with immunoglobulin G deficiency (IgGsd) often complain of fatigue. The correlation between systemic inflammation and fatigue is unknown. In this study perceived quality of life (QoL) and fatigue in individuals with IgGsd, on and off immunoglobulin replacement therapy (IgRT) were correlated to inflammatory markers in plasma to identify the subgroup that benefits from IgRT.MethodThirty-five IgGsd-patients were sampled on three occasions: at baseline, after being on IgRT for at least 18 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…The level of fatigue has previously been described in the present cohort [14]. Fatigue was evaluated by fatigue impact scale (FIS) [15], and FIS-score 60 or above was considered consistent with severe fatigue and was previously found to be associated with the need of IgRT [14]. Handling of blood samples and routine laboratory measurements Blood samples were drawn in vacutainers, and routine laboratory analyses and immune phenotyping were performed according to national treatment guidelines for IgGsd including levels of IgG, IgA, IgM, and IgG subclasses IgG1, IgG2 and IgG3 on fresh samples [11].…”
Section: Laboratory Parameters and Clinical Variables That Predict Ne...supporting
confidence: 61%
See 2 more Smart Citations
“…The level of fatigue has previously been described in the present cohort [14]. Fatigue was evaluated by fatigue impact scale (FIS) [15], and FIS-score 60 or above was considered consistent with severe fatigue and was previously found to be associated with the need of IgRT [14]. Handling of blood samples and routine laboratory measurements Blood samples were drawn in vacutainers, and routine laboratory analyses and immune phenotyping were performed according to national treatment guidelines for IgGsd including levels of IgG, IgA, IgM, and IgG subclasses IgG1, IgG2 and IgG3 on fresh samples [11].…”
Section: Laboratory Parameters and Clinical Variables That Predict Ne...supporting
confidence: 61%
“…4C). We have recently shown that fatigue is more common in IgGsd patients with need of IgRT in the present cohort of patients [14]. This led us to include severe fatigue among factors that may predispose for the need to reintroduce IgRT.…”
Section: Aggregated Factors That Predispose For the Need Of Igrtmentioning
confidence: 77%
See 1 more Smart Citation
“…VEGFA is a key regulator of vascular growth. Angiogenesis in skeletal muscle can maintain oxygen and nutrient supply and clear metabolic byproducts that may lead to fatigue ( Mohamad Shalan et al, 2016 ), which is associated with decreased levels of VEGFA ( Wågström et al, 2021 ). A study on metabolic gene polymorphisms conducted progressive fatigue tests on athletes and identified VEGFA rs2010963C as an “endurance allele” of elite athletes ( Ahmetov et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the serological indexes, the waterfall forest environment notably improved the levels of endogenous GSH-Px and SOD in participants but reduced the level of MDA. Meanwhile, the levels of serum IL-1β, IL-6, and IL-10 were decreased after exposure to the waterfall forest environment, suggesting that the waterfall forest environment can reduce the level of inflammatory factors in the body (34). Serum TNF-α level has been shown to be elevated in patients with agingrelated diseases such as Alzheimer disease (35).…”
Section: B Cmentioning
confidence: 99%